2017
DOI: 10.1016/j.cct.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of a multi-level mixed methods approach to study the effectiveness of a primary care progressive return to activity protocol after acute mild traumatic brain injury/concussion in the military

Abstract: The large number of U.S. service members diagnosed with concussion/mild traumatic brain injury each year underscores the necessity for clear and effective clinical guidance for managing concussion. Relevant research continues to emerge supporting a gradual return to pre-injury activity levels without aggravating symptoms; however, available guidance does not provide detailed standards for this return to activity process. To fill this gap, the Defense and Veterans Brain Injury Center released a recommendation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The short-and long-term consequences of TBI represent one of the most significant and complex challenges for the military healthcare system. 22,23 A TBI impacts force readiness in the short term, while a substantial number of veterans experience the consequences of TBI (and post-traumatic stress disorder [PTSD]) in the long term. 24 Dominant use of improvised explosive devices (IEDs) by insurgents against United States (US) military personnel during the latest military conflicts (and their continued use) have resulted in a staggering number of blast-induced TBI (bTBI) cases.…”
Section: Blast Scenariosmentioning
confidence: 99%
“…The short-and long-term consequences of TBI represent one of the most significant and complex challenges for the military healthcare system. 22,23 A TBI impacts force readiness in the short term, while a substantial number of veterans experience the consequences of TBI (and post-traumatic stress disorder [PTSD]) in the long term. 24 Dominant use of improvised explosive devices (IEDs) by insurgents against United States (US) military personnel during the latest military conflicts (and their continued use) have resulted in a staggering number of blast-induced TBI (bTBI) cases.…”
Section: Blast Scenariosmentioning
confidence: 99%
“…Data for this study were drawn from the broader DVBIC (Defense and Veterans Brain Injury Center, RRID:SCR_004505) PRA CR Study, which investigated the impact of implementing the DVBIC PRA CR focused on gradual return to unrestricted activity post-concussion among SMs (1, 14). The parent study has been previously described in detail (15). Data from the current study included only concussed SM participants who received “usual treatment” from providers who had not yet received focused training on the PRA CR.…”
Section: Methodsmentioning
confidence: 99%
“…Provider clinical practices and patient outcomes were examined before and after providers completed the training. 11 Results suggested that this training had a significant positive impact on clinical practices as well as on patients' recovery from concussion. 27 Interview data and informal feedback indicated that the training was well received and impacted concussion clinical practices as intended.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 96%
“…In a second phase of the DVBIC PRA study, we sought to evaluate the effects of directly training primary care providers on the DVBIC PRA CR. 11,27,32 Although the DVBIC PRA CR was publicly available online prior to training, providers indicated relatively low rates of exposure to this information before enrollment in the study. Concussion management clinical practices (including the likelihood of providing patient education) varied among primary care managers, both within and between the three military treatment facilities investigated.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 99%
See 1 more Smart Citation